2023
DOI: 10.1017/jns.2023.42
|View full text |Cite
|
Sign up to set email alerts
|

Rate, risk factors and estimations of time to develop severe acute malnutrition after children receiving antiretroviral therapy at selected health facilities in northwest Ethiopia

Abstract: Severe acute malnutrition (SAM) affects up to 50 % of children with HIV, especially those who reside in resource-constrained healthcare setting like Ethiopia. During subsequent follow-up of children factors related to incidence of SAM after antiretroviral therapy (ART) is set on, however, there is no prior evidence. An institution-based retrospective cohort study was employed among 721 HIV-positive children from 1 January to 30 December 2021. Data were entered using Epi-Data version 3.1 and exported to STATA v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In contrast to previous systematic review findings [ 53 , 55 ] and primary studies reported [ 12 , 17 , 32 , 33 , 38 , 57 60 ] this meta-regression found no significant association between declined CD4 count (≤200 cells/cml), age of patients, duration of follow-up, comorbidity status, and functional status with the risk developing active TB in HIV co-infection children. This might be related to the methodological differences, heterogeneity of included study populations, sample size limitations, publication bias, unaccounted factors, and further experimental studies are highly needed to better understand this relationship.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous systematic review findings [ 53 , 55 ] and primary studies reported [ 12 , 17 , 32 , 33 , 38 , 57 60 ] this meta-regression found no significant association between declined CD4 count (≤200 cells/cml), age of patients, duration of follow-up, comorbidity status, and functional status with the risk developing active TB in HIV co-infection children. This might be related to the methodological differences, heterogeneity of included study populations, sample size limitations, publication bias, unaccounted factors, and further experimental studies are highly needed to better understand this relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with previous studies finding in [ 12 , 17 , 32 , 33 , 38 , 57 60 ],concurrent administering of IPT after ruled-out of active TB symptoms with ART demoted more than 90% of active TB-associated incidence of morbidity [ 3 , 61 , 62 ]. In the final report of this systematic review and meta-analysis, it was found that HIV-infected children who did not receive IPT (preventive therapy) were at a twofold higher risk compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HIV- infection and undernutrion coexists in a viscous cycle and deadly duo with each one fuelling the other [ 11 , 20 ]. Children living with HIV are more vulnerable to undernutrition [ 21 ] due to several mechanisms: HIV- infection exposed children for decreased appetite [ 22 ], increase energy needs as a result of infection, exacerbating of gastrointestinal infections, enteropathy and food insecurity [ 20 ]. Moreover, children with HIV are prone to undernutrion due to reduced food intake resulting from decreased appetite [ 23 ], poor absorption of nutrients that result of recurrent or chronic diarrhea [ 24 ], increased energy needs as a result of virus replication and opportunistic infections [ 25 ].…”
Section: Introductionmentioning
confidence: 99%